2022
DOI: 10.1111/jfpe.14236
|View full text |Cite
|
Sign up to set email alerts
|

Determination and comparison of effective moisture diffusivity of carrot (core and cortex) during hot air drying

Abstract: The moisture content and shrinkage of a sample are often ignored when determining its effective moisture diffusivity (EMD), which will result in a larger error in simulating the dynamic moisture diffusion process during drying. This work aimed to determine the EMDs of cortex and core in axial and radial directions considering the combined influence of moisture content and shrinkage of material. The drying and shrinkage characteristics of cortex and core were investigated under different hot air drying conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Furthermore, the 2D-axiyometric and 3D contour plots in Table 6 reveal the realistic visualization of spatial temperature distribution at each location and non-isotropic shrinkage in axial and radial directions of slice. These findings may be confirmed by other reported studies (Ju et al, 2023;Zheng et al, 2023).…”
Section: Model Validationsupporting
confidence: 92%
“…Furthermore, the 2D-axiyometric and 3D contour plots in Table 6 reveal the realistic visualization of spatial temperature distribution at each location and non-isotropic shrinkage in axial and radial directions of slice. These findings may be confirmed by other reported studies (Ju et al, 2023;Zheng et al, 2023).…”
Section: Model Validationsupporting
confidence: 92%
“…Some studies showed that deformation and heat and mass transfer could not be studied separately, so the mathematical and geometric models were combined to discuss the effect of deformation on heat and mass transmission. Suvarnakuta et al (2007) The simulated drying results using effective moisture diffusion coefficient considering the moisture content and shrinkage were closer to the experimental results than that using the constant diffusion coefficient (Zheng et al, 2023). The simulated results of the hot air drying of shiitake mushroom and the microwave drying of potato based on the multiphase porous media models demonstrated the effect of deformation on heat and mass transmission (Gulati et al, 2016;Zhu et al, 2021).…”
mentioning
confidence: 58%
“…These results clearly demonstrate that increasing the temperature of the hot air significantly improves drying efficiency (Huishuang et al, 2020). Additionally, it is noteworthy that as the temperature of the hot air increases, the slope of the moisture content curve also increases, indicating a greater variation in grain drying rate with air temperature (Zhaohui et al, 2022). δ=σTtrueT¯×100%=1n1i=1nTiTtrue¯2trueT¯×100%, where δ is the temperature inhomogeneity coefficient; σT is the standard deviation of sampling points; Ttrue¯ is the average temperature of sampling points; n is the number of sampling points; Ti is the temperature of the i th sampling point.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 demonstrate that increasing the temperature of the hot air significantly improves drying efficiency (Huishuang et al, 2020). Additionally, it is noteworthy that as the temperature of the hot air increases, the slope of the moisture content curve also increases, indicating a greater variation in grain drying rate with air temperature (Zhaohui et al, 2022).…”
Section: Effect Of Different Hot Air Temperatures On the Drying Processmentioning
confidence: 99%